Binding of misacylated tRNAs to the ribosomal A site - DALE, TARAKA (Copyright 2005 by RNA Society, 2005)
To test whether the ribosome displays specificity for the esterified amino acid and the tRNA body of an aminoacyl-tRNA (aa-tRNA), the stabilities of 4 correctly acylated and 12 misacylated tRNAs in the ribosomal A site were determined. By introducing the GAC (valine) anticodon into each tRNA, a constant anticodon·codon interaction was maintained, thus removing concern that different anticodon·codon strengths might affect the binding of the different aa-tRNAs to the A site. Surprisingly, all 16 aa-tRNAs displayed similar dissociation rate constants from the A site. These results suggest that either the ribosome is not specific for different amino acids and tRNA bodies when intact aa-tRNAs are used or the specificity for the amino acid side chain and tRNA body is masked by a conformational change upon aa-tRNA release.